Identity and Interaction, A Glimpse into Persib WhatsApp Group - Dimas Yudhistira (MediaTor (Jurnal Komunikasi), 2021)
Persib Bandung, an Indonesian professional football club, is the place where several identities are encountered. The specific place discussed in this article is a virtual place namely WhatsApp group. This research illustrates the form of virtual interaction among the players and managers. The interaction form is connected with the identity markers of the players. To illustrate the  form of interaction in Persib’s WhatsApp group, I interviewed Persib’s social media manager. The aim of the questions is to uncover the activities inside the group. It makes this is a qualitative research. From the interview session, the data in the form of narration are discussed with the theory of identity, interaction, and social to find a meaning behind player’s responses towards messages from managers. As a result, Persib’s WhatsApp group is designed as a medium where the instructions are given. It shows that players’ understanding is influenced by their identity. The article finds the identity markers like age, race and experience enables the players to be more active in the group. However, identity markers like performance, which is seen as a salient aspect in football, do not guarantee the players to be more engaging in WhatsApp group.